To Disclose or Not to Disclose? Reasons for HIV Serostatus Disclosure and Non-disclosure by People Living with HIV/AIDS in Eastern India - Kansal, Sangeeta; Sarkar, Madhutandra; Kumar, Alok; Chakravarty, Jaya; Kumar, Rakesh (Indian Journal of Community Health, 2021)
Background: Understanding the reasons for HIV serostatus disclosure and nondisclosure and how these reasons differ by certain characteristics of the people living with HIV/AIDS (PLWHA) is important for effective HIV prevention intervention strategies. Objectives: This study was undertaken to investigate/identify the reasons for disclosure and nondisclosure of HIV serostatus by PLWHA, and to find out any association between the reasons for disclosure or nondisclosure and certain demographic and clinical characteristics, i.e. age, gender, WHO clinical stage and CD4 count of the study population. Methods: A cross-sectional study was conducted among all patients of 18-49 years with confirmed HIV infection registered at the antiretroviral therapy (ART) center of a tertiary care hospital in eastern Uttar Pradesh, India for one year, from July 2017 to June 2018. Results: The most common reason for disclosure of HIV serostatus was the presence of any family member at the time of collection of HIV test report (68.5%), and the most common reason for not disclosing the serostatus was stigmatization (68%). The reasons for disclosure was found to be associated with the WHO clinical stage of the respondents (p <0.05). Conclusions: The findings of this study highlights the need for tailoring intervention strategies for improving disclosure decision making according to the specific needs of PLWHA. There is also a need to address the concerns of those who are reluctant to disclose. More emphasis should be given on creating awareness about HIV stigma, on the importance of serostatus disclosure and secondary HIV prevention in the community.